Austria-Hungary and the Albanian project. A comparative case study: Between support and imperialism - Bezha, Anastas (Études sur la Région Méditerranéenne, 2020)
The purpose of this paper, is to analyze the role of the Austro-Hungarian Monarchy in the creation of Albania as a geopolitical entity and it’s continuity up until the end of World War I. This process is investigated by comparing two pivotal moments, that link the Danubian Monarchy and the Albanian nation and state-building processes, especially the conferences of 1896 by the officials of the Ballhausplatz and the conferences of the Common Ministeral Council (GMR) in January 1916. The paper is organized in three parts. The first one will introduce the shifting position of Austria-Hungary on the Eastern Question, regarding the methods and policies to be introduced via the local diplomatic Attaché in different consulates around the Albanian speaking vilayets. Additionally, it will highlight their role on moulding the Albanian latent nationalism into a political nation-building tool. The second part will investigate the Danubian Monarchy policy in the context of World War I and the controversial debates of the main imperial actors on the Albanian matter. The third part will compare the two above mentioned conferences and the shifting policies between colonization, imperial protectorate and independence. The importance of this paper is manifold. Primarily, it addresses the role of the Dual Monarchy in the creation of the Albanian state. Secondly, it points out the pragmatic reasons why the Dual Monarchy had to pursue these policies. Thirdly, it points out the diversity of opinions suggested by different imperial actors, which spanned from direct annexation, partial independence and partition of Albanian territories for geopolitical benefits. Fourthly, it’s a comparative study that has not been done regarding the two conferences, either from the Albanian or Austrian authors.